DSM Corp Sdn.Bhd / Ahmad Imran Zulkepli ... [et al.] - Zulkepli, Ahmad Imran; Ahmed Azizi, Ahmed Shahril; Zulkarnain, Muhammad Faris Aiman; Che Noor Azam, Muhammad Fauzan Rashidi; Syed Omar, Sharifah Arrysha (2021)
Every company have their own unique business name to make sure people in the industry known about their business. Thus, they will name their company base on what they have discussed with their partner. Our company also have their own unique name after and the name that we use are also have their own meaning. After discussed among ourselves, we decide to use DSM Corp Sdn.Bhd as our company name. It takes few days to decide what kind of name that the company must use to make sure the name are simple and easy for people or client to understand. DSM is a short term for Design, Social and Management. The name that we decide to use is related with the service that we will provide for customer. The business that we decide to run are based on digital art and design. We choose this kind of business because most of the share partner in this company are professionals in digital art and design. The company also provide digital printing for customer who want to make custom printing for their purpose. The digital printing service that we provide can be print on bunting, banner, business card, brochures, canvas and etc.DCM Corp Sdn.Bhd also provide photo shooting service for our customer. The company have their own studio in their building and the staff who responsible for the photo shooting is the share partner of the company. Customer can request many kinds of theme for their photo shoot and we will serve them after the deal has been made. Also, this company provide service for those who want their own website and their own application. Besides photo shooting and digital printing, the company will serve people who request to make their own website and application. Example of the job that we will consider to accept for website is the customer request us to build a website for a company to establish e-commerce services.